X-linked alpha-thalassemia/mental retardation (ATR-X) syndrome: a new kindred with severe genital anomalies and mild hematologic expression. - McPherson, E; Clemens, M; Gibbons, R; Higgs, D (1995)
We report a new kindred containing 4 patients with X-linked alpha-thalassemia/mental retardation syndrome ((ATR-X). Like previously reported ATR-X patients, these children are all genetic males with severe developmental delay and characteristic facial appearance. The genital anomalies are more severe than in most previous cases and have led to a female sex of rearing for 3 of the 4 patients. The hematologic expression is extremely mild and was not demonstrable on routine hematologic studies including hemoglobin electrophoresis, but the three living patients all had hemoglobin H inclusions on brilliant cresyl blue stained peripheral smears. The combination of skewed X-inactivation and haplotype analysis at Xq12-q21.3 confirmed carrier status in the 3 obligate carriers in the kindred and led to identification of an additional carrier. Two other women in the kindred appear to be noncarriers on the basis of normal X-inactivation and/or inheritance of a different Xq12-21.3 haplotype. More widespread use of brilliant cresyl blue staining for HbH inclusions in individuals with the facial phenotype of ATR-X and/or ambiguous genitalia may lead to the identification of more affected patients and improved understanding of the clinical spectrum of ATR-X.